Utilization of Forecasting Methods for Cryptocurrencies (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Electronic money has evolved in one of the relevant ways to achieve electronic payment, that is, a form of payment with significantly lower online transactions. The idea for the development of the above has consolidated the segment of retaining all the favourable characteristics of cash while eliminating deficiencies. The paper purpose is to discuss the relevance of electronic money or alternative currencies, cryptocurrencies, and to present statistical processing the most 30 influential cryptocurrencies with an emphasis on the most popular cryptocurrency called Bitcoin. We elaborate on the main differences between the virtual currency and electronic money after we present the historical development of cryptocurrencies. In the end, we present the statistical and forecasting analysis of the most important cryptocurrencies. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.